Higher Education’s Financial Sustainability: The Challenges for Private Higher Education in a Context of Rapid Change - Teixeira, Pedro (Rastros Rostros, 2026)
This text discusses key issues of financial sustainability in higher education, with a particular emphasis on the specific challenges and pressures faced by private universities. These include aspects relevant to the demand, such as demographic changes or the reconfiguration of higher education as a private good and an individual investment. It will also be examined how changing regulatory conditions have influenced institutional access to diverse streams of funding, particularly in a context of tightening competition within private higher education and between public and private higher education institutions, due to the blurring of boundaries between public and private institutions. Particular attention will be devoted to the organizational challenges associated with a strategy of financial sustainability based on a diverse revenue basis. This will range from issues such as organizational culture and governance to internal reward mechanisms and the capacity to develop coherent strategic and financial plans, all while institutions need to manage multiple funding streams. The analysis will also emphasize the importance of balancing academic and management priorities in a way that mitigates potential tensions and enhances internal cohesiveness and congruence with the mission. Thus, the analysis will emphasize more organizational and mission fulfillment issues rather than financial management ones. It will also reflect upon the former in a context of rapid technological and economic change that potentially challenges the relevance of higher education and introduces greater uncertainty for higher education institutions. The analysis will specifically address the challenges faced by private higher education. Although much of the recent expansion of private higher education has been characterized as a demand-absorption pattern, this type of expansion is not a sustainable development strategy. In post-massification cases, private institutions need to position themselves as an alternative to the public system, rather than a second choice for those who could not get a place in the latter. Furthermore, private HEIs need to engage much more in research activities, both as a strategy to strengthen their academic quality, to diversify their funding basis, or to foster their partnerships with external stakeholders. These transformations present significant institutional challenges and require particular attention to staff and organizational dimensions in order to become a more attractive institution to prospective students, funders, and other external stakeholders.
Keywords: Financial management; Diversification; Sustainability; Competition; Organizational Change